Electrode diaphragm as well as preparation method and application thereof
By using a combination of gel electrolyte, active particles, linear conductive agent and fiber binder in the dry electrode diaphragm, combined with neural nodes and neural network structure design, the problems of limited strength and large mechanical differences in traditional dry electrodes are solved, the resistivity reduction and mechanical performance improvement are achieved, and the industrialization process of dry electrodes is promoted.
Patent Information
- Application Number
- CN202411764041.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional dry electrodes have problems such as limited strength of the binder, large mechanical differences, and limited industrial promotion.
The electrode diaphragm consisting of gel electrolytes, active particles, linear conductive agents and fiber binders is designed through neural nodes and neural network structures, combined with hot rolling processing, forming a synergistic and double interpolation network to improve the mechanical properties and resistivity of the electrode diaphragm.
The mechanical difference between the electrode diaphragm in the calendering direction and the non-calendering direction is improved, the resistivity is reduced, the overall mechanical performance of the electrode diaphragm is enhanced, and the industrialization and promotion of dry electrodes is promoted.
Smart Images

Figure CN119673946A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrode membrane and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are mostly made using a slurry coating process, which consumes a lot of energy to dry the solvent during the preparation process. A new strategy is to use a solvent-free or low-solvent process to prepare dry electrodes and assemble them into batteries to reduce production costs. Among them, dry electrodes usually use polytetrafluoroethylene (PTFE) as a binder, using its fibrosis properties to form a self-supporting membrane structure with a certain strength.
[0003] However, the traditional dry-process electrode has limitations: (1) The PTFE binder itself has limited strength and will be oriented under directional shear, resulting in significant differences in the strength of the electrode in the calendering direction and the non-calendering direction; (2) In order to regulate the fiberization of all-dry powder PTFE, a semi-dry treatment method is usually used to introduce solvents to reduce the difficulty of fiberization, but a post-treatment step is required to remove the solvent after film formation, resulting in the failure to fully utilize the advantages of the dry process. In addition, the industrialization and promotion of dry-process electrodes is also affected by the difficulty of thinning the positive electrode material, the poor toughness of the film under high compaction, the high binder content, and the difficulty of liquid injection. Summary of the invention
[0004] Based on this, it is necessary to provide an electrode membrane and its preparation method and application to address the above problems; the electrode membrane described in the present invention has low resistivity and high strength, improves the mechanical difference between the rolling direction and the non-rolling direction, is particularly suitable for positive electrode sheets, and is conducive to industrial promotion.
[0005] An electrode membrane comprises: a gel electrolyte, active particles, a linear conductive agent and a fiber binder, wherein part of the linear conductive agent is coated on the surface of part of the active particles to form a neural node, and the neural node and the active particles are distributed in a neural network structure composed of the gel electrolyte, the linear conductive agent and the fiber binder.
[0006] In one of the embodiments, in the electrode membrane, the mass ratio of the gel electrolyte, the linear conductive agent, the fiber binder and the active particles is (12-25):(0.1-2):(1-5):(68-86.9).
[0007] In one embodiment, the gel electrolyte includes 10 wt % to 30 wt % of polymethyl methacrylate, 10 wt % to 30 wt % of lithium salt and the balance of ionic liquid.
[0008] In one embodiment, the melting point of the ionic liquid is less than or equal to 30°C;
[0009] And / or, the ionic conductivity of the ionic liquid is greater than 1×10 -4 S / cm;
[0010] And / or, the ionic liquid is selected from imidazole ionic liquids, and the imidazole ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0011] In one embodiment, the linear conductive agent is selected from at least one of carbon nanotubes, branched carbon black, and carbon nanotube fibers;
[0012] And / or, the fiber binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, and polyacrylic acid;
[0013] And / or, the active particles are selected from lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide.
[0014] A method for preparing the electrode membrane as described above comprises the following steps:
[0015] Mixing the gel electrolyte, the linear conductive agent and some active particles to obtain a first material;
[0016] performing a pre-fiberization treatment on the remaining active particles and the fiber binder to obtain a second material;
[0017] kneading the first material and the second material to obtain a third material;
[0018] The third material is subjected to hot roller pressing to obtain the electrode membrane.
[0019] In one embodiment, the mass of the part of active particles accounts for 10%-30% of the total mass of active particles in the electrode membrane;
[0020] And / or, the solid content of the first material is 20%-80%.
[0021] In one embodiment, the pre-fiberization treatment comprises: kneading at a temperature of 60°C-100°C and a rotation speed of 10rpm-50rpm;
[0022] And / or, the kneading treatment comprises: kneading at a temperature of 60°C-100°C and a rotation speed of 5rpm-10rpm;
[0023] And / or, the hot rolling treatment includes: first thinning to a target thickness at 60°C-100°C, and then rolling at 120°C-150°C, with a rolling speed of 0.5m / min-10m / min.
[0024] An electrode plate comprises a current collector and the electrode membrane as described above which is stacked on the surface of the current collector.
[0025] An energy storage device comprises the electrode plate as described above.
[0026] The electrode diaphragm described in the present invention, on the one hand, fully utilizes the advantages of the linear conductive agent through the dispersing effect of the gel electrolyte on the linear conductive agent, can help build a network phase structure with better mechanical stability, and is compounded with the fiber binder to form a synergistic effect and a double interpenetrating network, which can effectively avoid the limitations of a single binder network, enhance the overall mechanical performance of the electrode diaphragm, ensure the strength in the non-calendering direction, and improve the mechanical difference of the electrode diaphragm in the calendering direction and the non-calendering direction; on the other hand, by establishing neural nodes as a series connection, the bridging function of the linear conductive agent is guaranteed, the difficulty of laying the conductive agent network is reduced, and it is beneficial to improve the resistivity of the electrode diaphragm.
[0027] In addition, the gel electrolyte introduced into the electrode membrane can maintain the semi-dry state of the material without removal. As a pre-injection component, it can also improve the injection efficiency. This not only effectively solves the limitations of traditional dry-process electrodes, but also makes the electrode membrane more processable. For high-hardness positive electrode active particle materials, it can easier to achieve thinning of the support membrane and increase the compaction density, which is conducive to industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 A schematic diagram of the structure of an electrode membrane in one embodiment of the present invention;
[0030] Figure 2 is a scanning electron microscope image of a neural node in one embodiment of the present invention;
[0031] Figure 3 It is a comparison chart of the film mechanical properties of the electrode membranes prepared in Example 1 and Comparative Example 3, and Example 4 and Comparative Example 4 in the calendering and vertical directions.
[0032] Among them, 1. Neural network structure; 2. Neural nodes; 3. Active particles. DETAILED DESCRIPTION
[0033] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0035] The present invention provides an electrode membrane, comprising: a gel electrolyte, active particles 3, a linear conductive agent and a fiber binder, Figure 1 As shown, part of the linear conductive agent is coated on the surface of part of the active particles 3 to form a neural node 2, and the neural node 2 and the active particles 3 are distributed in a neural network structure 1 composed of the gel electrolyte, the linear conductive agent and the fiber binder.
[0036] The electrode membrane of the present invention overcomes the agglomeration problem of the linear conductive agent in the full dry process through the dispersion effect of the gel electrolyte on the linear conductive agent, gives full play to the advantages of the linear conductive agent, and based on the design of the neural node 2, further reduces the difficulty of laying the linear conductive agent network in the membrane structure, thereby improving the resistivity of the electrode membrane. At the same time, the network is compounded with the fiber binder to form a synergistic effect and a double interpenetrating network, which can help effectively gather the active particles 3, improve the overall mechanical performance of the electrode membrane, and avoid the mechanical weakening problem in the non-calendering direction caused by the orientation of the fiber bonding network during the calendering process, and balance the mechanical differences between the electrode membrane in the calendering direction and the non-calendering direction.
[0037] In addition, the gel electrolyte introduced into the electrode membrane can maintain the semi-dry state of the material without removal. As a pre-injection component, it can also improve the injection efficiency. This not only effectively solves the limitations of traditional dry-process electrodes, but also makes the electrode membrane more processable. For high-hardness positive electrode active particle materials, it can easier to achieve thinning of the support membrane and increase the compaction density, which is conducive to industrial promotion.
[0038] It should be noted that the distribution states of the neural nodes 2 and the active particles 3 in the neural network structure 1 can be the same or different. For example, both the neural nodes 2 and the active particles 3 can be connected to the neural network structure 1, and the active particles 3 can also be independently distributed in the gaps of the neural network structure 1.
[0039] In one embodiment, in the electrode membrane, the mass ratio of the gel electrolyte, the linear conductive agent, the fiber binder and the active particles 3 is (12-25):(0.1-2):(1-5):(68-86.9), including but not limited to any point value among 12:0.5:1:86.5, 15:0.5:1:83.5, 18:1:1:80, 20:1:2:77, 22.5:0.5:2:75 or the range value between any two of them.
[0040] In one embodiment, the gel electrolyte includes polymethyl methacrylate, lithium salt and ionic liquid, wherein the ionic liquid, on the one hand, is a good medium for dispersing linear conductive agents. Under the action of cations and π bonds or π-π forces, the ionic liquid can be adsorbed onto the surface of the linear conductive agent to form ion clusters, thereby preventing the linear conductive agent from agglomerating; on the other hand, it is beneficial to maintain the semi-dry state of the material and ensure the semi-dry processing strategy. Moreover, the ionic liquid does not need to be removed in subsequent processes and can be used as a pre-injection component to improve the injection efficiency.
[0041] Preferably, in the gel electrolyte, the mass fraction of polymethyl methacrylate is 10wt%-30wt%, which is beneficial to improving the flexibility of the electrode membrane; the mass fraction of lithium salt is 10wt%-30wt%, and the balance is ionic liquid.
[0042] It should be noted that the present invention does not limit the polymethyl methacrylate in the gel electrolyte, and the polymethyl methacrylate can be directly used or obtained by formulation.
[0043] Preferably, the polymethyl methacrylate is prepared from methyl methacrylate and an initiator, so that the polymethyl methacrylate and the ionic liquid are fully miscible without introducing an additional organic solvent for dissolution and preparation, wherein the initiator includes but is not limited to azobisisobutyronitrile (AIBN).
[0044] Preferably, the melting point of the ionic liquid is less than or equal to 30°C, more preferably less than 0°C.
[0045] Preferably, the ionic conductivity of the ionic liquid is greater than 1×10 -4 S / cm, including but not limited to 2.2×10 - 4S / cm, 5.0×10 -4 S / cm, 8.2×10 -4 S / cm, 1.0×10 -3 S / cm, 1.2×10 -3 S / cm, or any range between them.
[0046] Preferably, the ionic liquid is selected from imidazole ionic liquids, which are more conducive to dispersing the linear conductive agent and reducing the aggregation of the linear conductive agent.
[0047] Specifically, the imidazolium ionic liquid is composed of imidazolium cations and inorganic / organic anions, wherein the imidazolium cations include but are not limited to methyl imidazole, ethyl imidazole, butyl imidazole, etc., and the anions include but are not limited to tetrafluoroborate, hexafluorophosphate, bis(trifluoromethanesulfonyl)imide, etc.
[0048] More preferably, the imidazole ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0049] Preferably, the lithium salt is selected from lithium bis(trifluoromethane)sulfonyl imide (LiTFSI).
[0050] In one embodiment, the linear conductive agent is selected from at least one of carbon nanotubes, branched carbon black, and carbon nanotube fibers. When the linear conductive agent is selected from carbon nanotubes, it is preferably a single-walled carbon nanotube. Further preferably, the length of the single-walled carbon nanotube is 1 μm-50 μm, including but not limited to any point value among 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 20 μm, and 50 μm, or a range value between any two of them.
[0051] In one embodiment, the fiber binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, and polyacrylic acid, preferably polytetrafluoroethylene.
[0052] It is understandable that the electrode membrane can be used for the positive electrode or the negative electrode, and the present invention does not limit this. For example, when the active particles 3 use positive electrode active materials, the electrode membrane is suitable for the positive electrode; when the active particles 3 use negative electrode active materials, the electrode membrane is suitable for the negative electrode.
[0053] In one embodiment, the active particles are selected from lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide. Preferably, the median particle size (D50) of the active particles is 4 μm-15 μm, including but not limited to any point value among 4 μm, 5 μm, 6.8 μm, 8 μm, 10 μm, 12 μm, and 15 μm, or a range value between any two of them.
[0054] The present invention provides a method for preparing the electrode membrane as described above, comprising the following steps:
[0055] S1, mixing a gel electrolyte, a linear conductive agent and a portion of active particles to obtain a first material;
[0056] S2, pre-fiberizing the remaining active particles and the fiber binder to obtain a second material;
[0057] S3, kneading the first material and the second material to obtain a third material;
[0058] S4, subjecting the third material to a hot roller pressing process to obtain the electrode membrane.
[0059] Taking into account that in the traditional dry electrode process, the agglomeration problem of the linear conductive agent greatly limits its addition and use, therefore, in step S1 of the present invention, a solvent-free dispersion strategy is adopted to simplify the addition process of the linear conductive agent and pre-construct a dispersed conductive network to facilitate the subsequent bridging function. At the same time, by introducing some active particles to act as grinding media, it helps to improve the grinding efficiency on the one hand, and helps to modify the active particles on the other hand, serving as a connection transit point for the network.
[0060] In one embodiment, the mass of the partial active particles accounts for 10%-30% of the total mass of the active particles in the electrode membrane, including but not limited to any point value of 10%, 15%, 20%, 30% or any range value therebetween.
[0061] In one embodiment, the solid content of the first material is 20%-80%, including but not limited to any value among 20%, 30%, 40%, 50%, 60%, 80% or any range between two values.
[0062] In one embodiment, the gel electrolyte includes 10wt%-30wt% of polymethyl methacrylate, 10wt%-30wt% of lithium salt and the remainder of ionic liquid, wherein the ionic liquid, on the one hand, is a good medium for dispersing linear conductive agents. Under the action of cations and π bonds or π-π forces, the ionic liquid can be adsorbed onto the surface of the linear conductive agent to form ion clusters, thereby preventing the linear conductive agent from agglomerating; on the other hand, it can maintain the semi-dry state of the material and ensure the semi-dry processing strategy. Moreover, the ionic liquid does not need to be removed in subsequent processes and can be used as a pre-injection component to improve the injection efficiency.
[0063] It should be noted that the present invention does not limit the polymethyl methacrylate in the gel electrolyte, and the polymethyl methacrylate can be obtained by preparation or directly used. When the polymethyl methacrylate is obtained by preparation, the ionic liquid, the linear conductive agent and part of the positive electrode active particles can be ground into a jelly state, and then the lithium salt and the polymer monomer and initiator required for preparing the polymethyl methacrylate are added and ground evenly; when the polymethyl methacrylate is directly used, the polymethyl methacrylate in the gel electrolyte can also be added in step S2 to achieve a similar effect as a pore-forming agent, which is conducive to promoting the composite of the two-phase network in step S3.
[0064] Preferably, the ionic liquid is selected from imidazole ionic liquids, which are more conducive to dispersing the linear conductive agent and reducing the aggregation of the linear conductive agent.
[0065] More preferably, the imidazole ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0066] Preferably, the lithium salt is selected from lithium bis(trifluoromethane)sulfonyl imide (LiTFSI).
[0067] In step S2, pre-fiberization treatment is beneficial to improve the controllability of the process. Although the advantage of semi-dry treatment over full dry treatment is that it improves the kneading effect of materials and is more convenient to form a paste, in the process of PTFE fiberization regulation by mixing, the introduction of liquid matrices such as solvents will greatly reduce the shear resistance. Although it will not affect the kneading of the materials, it will cause the PTFE fibers in the formed paste to be actually of varying quality. Therefore, the present invention separates the fiber regulation and kneading processes, and first constructs a bonding network, which is beneficial to improving the subsequent kneading quality.
[0068] In one embodiment, the method of mixing the gel electrolyte, the linear conductive agent and a portion of the active particles comprises: grinding at a temperature below 20°C.
[0069] In one embodiment, the pre-fiberization treatment method includes: kneading at a temperature of 60°C-100°C and a rotation speed of 10rpm-50rpm. Specifically, the rotation speed includes but is not limited to any point value among 10rpm, 12rpm, 14rpm, 15rpm, 18rpm, 20rpm, 40rpm or any range value between two of them.
[0070] It should be noted that the pre-fiberization process needs to avoid the material from forming a paste-like material. The best state is when the appearance of the material in the cavity changes from a powdery state with undulating particles to a thin film-like state.
[0071] In step S3 and step S4, the neural network structure formed by kneading the first material and the second material not only improves the strength of the electrode membrane and improves the mechanical difference between the rolling direction and the non-rolling direction, but also gives full play to the advantages of the dry method, which is conducive to promoting the industrialization process of dry-process electrodes.
[0072] In one embodiment, the kneading treatment method includes: kneading at a temperature of 60°C-100°C and a rotation speed of 5rpm-10rpm. Specifically, the rotation speed includes but is not limited to any point value among 5rpm, 6rpm, 7rpm, 8rpm, 9rpm, 10rpm or any range value between two of them; the kneading time is preferably 5min-15min, including but not limited to any point value among 5min, 6min, 7min, 8min, 10min or any range value between two of them.
[0073] In one embodiment, the hot rolling treatment method includes: first thinning to a target thickness at 60°C-100°C to improve compaction, and then rolling at 120°C-150°C to improve bonding and cross-linking effects. The rolling speed is 0.5m / min-10m / min, including but not limited to any point value among 0.5m / min, 1m / min, 2m / min, 3m / min, 5m / min, 8m / min, 10m / min or any range value between two of them.
[0074] The present invention provides an electrode sheet, comprising a current collector and an electrode membrane as described above stacked on the surface of the current collector. It is understandable that, according to the different active particles selected in the electrode membrane, the electrode sheet is divided into a positive electrode sheet and a negative electrode sheet, for example: when the active particles are selected from lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide or lithium cobalt oxide, the electrode sheet is a positive electrode sheet; when the active particles are selected from porous carbon or silicon carbon composite materials, the electrode sheet is a negative electrode sheet.
[0075] The present invention also provides an energy storage device, comprising the electrode plate as described above. It is understandable that the energy storage device includes but is not limited to a battery.
[0076] The electrode membrane, its preparation method and application are further described below by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0077] Example 1
[0078] Step 1: Take 0.5 parts of single-walled carbon nanotube powder with a length of 10 μm and add it to 15 parts of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (melting point is -15°C, ionic conductivity is 9.2×10 -3 S / cm), and then 10 parts of lithium nickel cobalt manganese oxide with a median particle size of 9 μm were added for primary grinding, and then 3 parts of polymethyl methacrylate (prepared with methyl methacrylate and initiator azobisisobutyronitrile in a mass ratio of 100:1) and 4.5 parts of LiTFSI were added for secondary grinding for 10 minutes, so that the material was finally in a gel state with a solid content of 55%.
[0079] Step 2: Take another 65 parts of lithium nickel cobalt manganese oxide and 2 parts of PTFE and knead them at 80°C at a speed of 10 rpm to pre-fiberize the PTFE and then add it to the material obtained in step 1. Then reduce the kneading speed to 5 rpm, knead at 80°C for 6 minutes and take out the material. The material was tested for morphology, and the results are as follows: Figure 2 As shown, it can be seen that the linear conductive agent is coated on the surface of the active particles and extends in a branched shape, forming bridges with other active particles or fiber binders, similar to nerve nodes.
[0080] Step 3: The material taken out in step 2 is hot rolled, firstly continuously thinned and compacted at 80°C at a speed of 5m / min until the thickness is 120μm, and then finally rolled at 120°C at a working speed of 0.5m / min with the same thickness gap to obtain an electrode membrane.
[0081] Example 2
[0082] The difference between Example 2 and Example 1 is that in step 1, 12 parts of 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide and 2.5 parts of LiTFSI are used, and the rest remain unchanged; in step 2, 70 parts of lithium nickel cobalt manganese oxide particles are used, and the rest remain unchanged.
[0083] Example 3
[0084] The difference between Example 3 and Example 1 is that the length of the single-walled carbon nanotube powder used is 2 μm.
[0085] Example 4
[0086] The difference between Example 4 and Example 1 is that lithium iron phosphate particles are used instead of lithium nickel cobalt manganese oxide, and the median particle size is 7 μm.
[0087] Example 5
[0088] The difference between Example 5 and Example 1 is that in step 1, 0.5 parts of Ketjen black and 8 parts of 1-butyl-3-methylimidazolium hexafluorophosphate (melting point is -8°C, conductivity is 1.37×10 -3 S / cm), 1.5 parts of PMMA, 3 parts of LiTFSI, and the rest remain unchanged, with a solid content of 65%; 75 parts of lithium nickel cobalt manganese oxide are used in step 2.
[0089] Comparative Example 1
[0090] Step 1: Take 0.5 parts of single-walled carbon nanotube powder with a length of 10 μm, add it to 15 parts of 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide and mix and grind, then add 3 parts of polymethyl methacrylate (prepared with methyl methacrylate and initiator azobisisobutyronitrile in a mass ratio of 100:1) and 4.5 parts of LiTFSI and grind again for 10 minutes, and the solid content is 35%.
[0091] Step 2: Take 75 parts of lithium nickel cobalt manganese oxide and 2 parts of PTFE and knead them at 80°C at a rate of 10 rpm to pre-fiberize the PTFE and then add it to the material obtained in step 1. Then reduce the kneading speed to 5 rpm, knead at 80°C for 6 minutes and take out the material.
[0092] Step 3: The material taken out in step 2 is hot rolled, firstly continuously thinned and compacted at 80°C at a speed of 5m / min until the thickness is 120μm, and then finally rolled at 120°C at a working speed of 0.5m / min with the same thickness gap to obtain an electrode membrane.
[0093] Comparative Example 2
[0094] The difference between Comparative Example 2 and Comparative Example 1 is that 12 parts of 1-ethyl-3-methylimidazole bis(trifluoromethylsulfonyl)imide and 2.5 parts of LiTFSI are used in step 1, and the rest remain unchanged; 80 parts of lithium nickel cobalt manganese oxide particles are used in step 2, and the rest remain unchanged.
[0095] Comparative Example 3
[0096] Step 1: Take 0.5 parts of single-walled carbon nanotube powder with a length of 10 μm, add it to 18 parts of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and mix, then add 10 parts of lithium nickel cobalt manganese oxide with a median particle size of 9 μm for initial grinding, and then add 4.5 parts of LiTFSI for secondary grinding for 10 minutes, so that the material is finally in a gel state with a solid content of 45%.
[0097] Step 2: Take another 65 parts of lithium nickel cobalt manganese oxide and 2 parts of PTFE and knead them at 80°C at a rate of 10 rpm to pre-fiberize the PTFE and then add it to the material obtained in step 1. Then reduce the kneading speed to 5 rpm, knead at 80°C for 6 minutes and take out the material.
[0098] Step 3: The material taken out in step 2 is hot rolled, firstly continuously thinned and compacted at 80°C at a speed of 5m / min until the thickness is 120μm, and then finally rolled at 120°C at a working speed of 0.5m / min with the same thickness gap to obtain an electrode membrane.
[0099] Comparative Example 4
[0100] The difference between Comparative Example 4 and Comparative Example 3 is that lithium iron phosphate particles are used instead of lithium nickel cobalt manganese oxide, and the median particle size is 7 μm.
[0101] Comparative Example 5
[0102] Take 0.5 parts of single-walled carbon nanotube powder with a length of 10 μm, mix it thoroughly with 1.5 parts of carbon black powder and 96 parts of nickel cobalt manganese oxide, then add 2 parts of PTFE and mix them evenly. Perform banburying treatment at 80°C, a speed of 10 rpm, and a time of 10 minutes to fully fiberize the PTFE. Then, the material is gradually hot rolled at 120°C and 0.5 m / min and thinned to 120 μm.
[0103] The mechanical properties of the electrode membranes prepared in Example 1 and Comparative Example 3, and in Example 4 and Comparative Example 4 were compared in the calendering and vertical directions. The results are as follows: Figure 3 As shown, it is obvious that the electrode diaphragm of Example 1 has better film mechanical properties in both calendering and vertical directions than those of Comparative Example 3, and the electrode diaphragm of Example 4 has better film mechanical properties in both calendering and vertical directions than those of Comparative Example 4. In addition, the difference in film mechanics between calendering and vertical directions between the electrode diaphragms of Example 1 and Example 4 is small, while the difference in film mechanics between calendering and vertical directions between the electrode diaphragms of Comparative Example 3 and Comparative Example 4 is large.
[0104] The electrode membranes prepared in all the embodiments and comparative examples were assembled into button half-cells and subjected to performance tests. The results are shown in Table 1.
[0105] Assemble the battery: The electrode membrane and the carbon-coated current collector are coated at 80°C, compacted, cut into small discs, and then assembled in the order of lithium metal sheet / diaphragm / positive electrode sheet to make CR2032 batteries for standby testing.
[0106] Test: Thin film resistivity is tested directly on the positive electrode film (without film coating) using a four-probe device; the battery test uses 0.1c constant current charge and discharge for the first 5 cycles, first charging and then discharging, with a voltage range of 2.8V-4.2V for lithium nickel cobalt manganese oxide and 2.0V-3.75V for lithium iron phosphate, and then changes to 0.5c constant current charge and discharge after the test is completed.
[0107] Table 1
[0108]
[0109] According to Table 1, the electrode membrane provided by the present invention has both low resistivity and high capacity, and can be successfully applied to positive electrode sheets, effectively solving the limitations of current dry-process electrodes. However, due to the lack of grinding media, the film resistivity of Comparative Examples 1 and 2 increased at the same grinding and dispersion time, which may be affected by the insufficient laying of the internal carbon nanotube network; Comparative Examples 3 and 4 did not form PMMA cross-links in the gel electrolyte, which on the one hand led to poor mechanical stability in the vertical direction of the membrane, and on the other hand, the overall electrochemical cycle performance of the membrane was poor; Comparative Example 5 adopted a full dry process, resulting in poor membrane resistivity and initial efficiency, which may be affected by insufficient electrolyte infiltration.
[0110] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0111] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An electrode membrane, characterized in that: include: Gel electrolyte, active particles, linear conductive agent and fiber binder, wherein part of the linear conductive agent is coated on the surface of part of the active particles to form neural nodes, and the neural nodes and the active particles are distributed in a neural network structure composed of the gel electrolyte, the linear conductive agent and the fiber binder.
2. The electrode membrane according to claim 1, characterized in that: In the electrode membrane, the mass ratio of the gel electrolyte, the linear conductive agent, the fiber binder and the active particles is (12-25):(0.1-2):(1-5):(68-86.9).
3. The electrode membrane according to claim 1 or 2, characterized in that: The gel electrolyte includes 10 wt % to 30 wt % of polymethyl methacrylate, 10 wt % to 30 wt % of lithium salt and the balance of ionic liquid.
4. The electrode membrane according to claim 3, characterized in that: The melting point of the ionic liquid is less than or equal to 30°C; And / or, the ionic conductivity of the ionic liquid is greater than 1×10 -4 S / cm; And / or, the ionic liquid is selected from imidazole ionic liquids, and the imidazole ionic liquid is selected from at least one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium hexafluorophosphate.
5. The electrode membrane according to claim 1 or 2, characterized in that: The linear conductive agent is selected from at least one of carbon nanotubes, branched carbon black, and carbon nanotube fibers; And / or, the fiber binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyethylene oxide, and polyacrylic acid; And / or, the active particles are selected from lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide.
6. A method for preparing an electrode membrane according to any one of claims 1 to 5, characterized in that: The steps include: Mixing the gel electrolyte, the linear conductive agent and some active particles to obtain a first material; performing a pre-fiberization treatment on the remaining active particles and the fiber binder to obtain a second material; kneading the first material and the second material to obtain a third material; The third material is subjected to hot roller pressing to obtain the electrode membrane.
7. The method for preparing an electrode membrane according to claim 6, characterized in that: The mass of the part of active particles accounts for 10%-30% of the total mass of active particles in the electrode membrane; And / or, the solid content of the first material is 20%-80%.
8. The method for preparing an electrode membrane according to claim 6, characterized in that: The pre-fiberization treatment method includes: performing banburying at a temperature of 60°C-100°C and a rotation speed of 10rpm-50rpm; And / or, the kneading treatment comprises: kneading at a temperature of 60°C-100°C and a rotation speed of 5rpm-10rpm; And / or, the hot rolling treatment includes: first thinning to a target thickness at 60°C-100°C, and then rolling at 120°C-150°C, with a rolling speed of 0.5m / min-10m / min.
9. An electrode plate, characterized in that: It comprises a current collector and an electrode membrane as described in any one of claims 1 to 5 stacked on the surface of the current collector.
10. An energy storage device, characterized in that: Comprising the electrode plate as described in claim 9.